2013
DOI: 10.1002/per.1894
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Big Five Personality Measurements for Acquiescence: An 18–Country Cross–Cultural Study

Abstract: For groups of persons with low or medium levels of education, Big Five personality scales typically yield scores that poorly replicate the idealized Big Five factor pattern. On the basis of representative samples of German adults, Rammstedt et al. have demonstrated that correcting each person's score for acquiescence eliminates this problem. In the present 18-country study using large samples representative of each country's adult population, we found that, in all cases, correcting for acquiescence did indeed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 33 publications
6
73
0
7
Order By: Relevance
“…This can substantially bias correlations between items (Bentler et al, 1971), factor structures of personality inventories (Aichholzer, 2014;Rammstedt & Farmer, 2013), comparability of personality assessments across countries (Rammstedt, Kemper, & Borg, 2013) and (as shown in the present research) the suitability of underlying measurement models, and bias the correlation between personality items and criterion variables. Therefore, acquiescence should not be ignored (cf.…”
Section: Controlling Acquiescencementioning
confidence: 92%
“…This can substantially bias correlations between items (Bentler et al, 1971), factor structures of personality inventories (Aichholzer, 2014;Rammstedt & Farmer, 2013), comparability of personality assessments across countries (Rammstedt, Kemper, & Borg, 2013) and (as shown in the present research) the suitability of underlying measurement models, and bias the correlation between personality items and criterion variables. Therefore, acquiescence should not be ignored (cf.…”
Section: Controlling Acquiescencementioning
confidence: 92%
“…Moreover, acquiescence can spuriously inflate item covariances, thereby distorting any covariance‐based statistics such as reliability estimates, factor structures and correlations (e.g., Danner, Aichholzer, & Rammstedt, ; Lechner & Rammstedt, ). These issues are particularly pressing in research comparing (sub‐)populations that differ in their levels of acquiescence, such as different educational strata (Rammstedt & Farmer, ) or national cultures (Rammstedt, Kemper, & Borg, ). Unless corrected by balanced‐keyed scales (i.e., positively and negatively keyed items; Lechner & Rammstedt, ; Plieninger, ) and proper modelling strategies (e.g., a latent acquiescence factor; Billiet & McClendon, ), acquiescence can lead to erroneous conclusions about the measurement equivalence or group differences in constructs of interest (Buckley, ; van Vlimmeren, Moors, & Gelissen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have focused on respondent characteristics. Lower educational attainment (Narayan & Krosnick, ; Rammstedt et al ., ) and cognitive ability (Lechner & Rammstedt, ; Zhou, McClendon, & Zhou, ) show particularly robust relationships with higher acquiescence. In addition, studies have found small age‐related increases in acquiescence (Meisenberg & Williams, ; Weijters, Geuens, & Schillewaert, ).…”
Section: Introductionmentioning
confidence: 99%
“…Esto se respalda con los trabajos que corroboran su carácter intercultural a nivel sustantivo (McCrae & Terracciano, 2005;Schmitt, Allik, McCrae & Benet-Martínez, 2007; Yamagata et al, 2006) e, incluso, en relación a estilos de respuesta, como el aquiescente (Rammstedt, Kemper & Borg, 2013). Sin embargo, aunque los resultados de algunos estudios sean divergentes a la premisa de replicabilidad intercultural (Fetvadjiev & van der Vijver, 2015;Gurven, von Rueden, Massenkoff, Kaplan & Lero Vie, 2013;Schmitt et al, 2007) La correspondencia relativa a este artículo debe ser dirigida a…”
Section: Modelo De Los Cinco Grandes Factoresunclassified
“…Esto se respalda con los trabajos que corroboran su carácter intercultural a nivel sustantivo (McCrae & Terracciano, 2005;Schmitt, Allik, McCrae & Benet-Martínez, 2007;Yamagata et al, 2006) e, incluso, en relación a estilos de respuesta, como el aquiescente (Rammstedt, Kemper & Borg, 2013). Sin embargo, aunque los resultados de algunos estudios sean divergentes a la premisa de replicabilidad intercultural (Fetvadjiev & van der Vijver, 2015;Gurven, von Rueden, Massenkoff, Kaplan & Lero Vie, 2013;Schmitt et al, 2007), se concluye que la replicación del modelo de los 5GF parece ser más robusta en sociedades occidentales, con educación formal, industrializadas, pudientes y democráticas (Henrich, Heine & Norenzayan, 2010), así como en población universitaria o con grado de instrucción elevado (Rammstedt, Kemper & Borg, 2013) y con edades cercanas a la adultez (Soto, John, Gosling & Potter, 2008), al ser menos susceptibles a mostrar sesgos de respuesta.…”
Section: Modelo De Los Cinco Grandes Factoresunclassified